An analysis of randomised controlled trials that utilise internet based smoking reduction/cessation programs. (2015) - Prybutok, Gayle
Consumer health informatics (CHI) uses Internet based systems to deliver health education/intervention programs to the public. Smoking reduction/cessation efforts improve public health and reduce healthcare costs. Scientists believe that smoking avoidance/cessation before age 30 can prevent over 90% of smoking related cancers. Approaches to reducing smoking related deaths include encouraging current smokers to stop and preventing new people from smoking. The Agency for Healthcare Research and Quality (AHRQ) Clinical Evidence Topic 188, impact of CHI applications, prompted an analysis of a defined group of randomised controlled trials (RCTs) that examined Internet smoking reduction/cessation interventions using the techniques defined for Evidence Based Practice. A search of the University EBSCO Host databases, PubMed, the Cochrane Library, and EMBASE identified 13 RCTs summarising the outcomes of 17 internet based smoking reduction/cessation programs between 2006 and 2015. These programs were shown to be promising tools in the smoking reduction/cessation effort.